2021
DOI: 10.1371/journal.pone.0249003
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of hepatocellular carcinoma post proton beam therapy using MRI as an early prediction of treatment effectiveness

Abstract: Purpose To demonstrate the feasibility of magnetic resonance imaging (MRI) for early prediction of proton beam therapy (PBT) effectiveness in hepatocellular carcinoma (HCC). Methods Clinical data of the HCC patients without regional lymph node involvement or distant metastasis who received PBT at this institution between 2014 and 2017 were reviewed. A total of 43 patients were included. Tumor regression pattern after PBT were examined on the basis of follow-up duration. The variables were compared between pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Cases that reached CR/PR at 6 and 12 months had significantly better OS compared to non-CR/non-PR cases. Lin et al also found that HCC treated with PBT reached had better OS in CR cases at 3 months in MRI follow-up [23]. Intrahepatic recurrence outside the irradiated field is a common cause of death after PBT for HCC; thus, non-CR cases may be at high risk for this recurrence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cases that reached CR/PR at 6 and 12 months had significantly better OS compared to non-CR/non-PR cases. Lin et al also found that HCC treated with PBT reached had better OS in CR cases at 3 months in MRI follow-up [23]. Intrahepatic recurrence outside the irradiated field is a common cause of death after PBT for HCC; thus, non-CR cases may be at high risk for this recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Takahashi et al reported that a difference in CT values between post-treatment lesions and liver parenchyma in the portal phase at 1-2 years after PBT is a predictor of local recurrence [22]. Lin et al found a median time to resolution of early enhancement on MRI of 5 months after PBT [23]. In this study, the presence of early enhancement at 6 months after PBT was not related to MST (presence vs. absence: 38.4 vs. 41.9 months, p = 0.147), but was significant at 12 and 24 months.…”
Section: Discussionmentioning
confidence: 99%